Dampak undang-undang nomor 4 tahun 2023 tentang pengembangan dan penguatan sektor keuangan (P2SK) terhadap kelangsungan sektor jasa keuangan khususnya sektor lembaga pembiayaan - Anggraeni, Devi; Pratomo, Wisnu Budhi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The current pattern of city development is influenced by various aspects, one of which greatly affects the development is the development of the economic sector. The financial services sector which is one of the pillars of people's lives has led to very rapid development and of course, this is also what ultimately raises many problems in the financial sector, especially fundamental problems. The purpose of this study is to determine the impact of law number 4 of 2023 on the sustainability of the financial services sector, especially the financing institution sector. This research was conducted with a qualitative approach and is descriptive in nature with data collection tools, namely in-depth and gradual interviews. The results obtained are Law No. 4 of 2023 can optimize the intermediary function to productive sector businesses, increase inclusion and literacy of the financial services sector, develop and strengthen the financial sector ecosystem, and be able to create synergy and good coordination between regulators and increase community competitiveness so that they can do business effectively and efficiently.